Nyström least-squares collocation for regional geoid modeling with a large dataset - Xun Zhang; Guobin Chang; Hefang Bian; Xiannan Han; Houpu Li (Earth Science Informatics, 2026)

Physical structure and hydraulic characteristics of porous ceramics for water potential sensors: Influence of material particle size and moulding pressure - Chunhao Fang; Haitao Wang; Xiaoyang Liang; Jiandong Wang; Xin Han; Guobin Wang (Biosystems Engineering, 2026)

Design and optimisation of differentiated UAV-based fertiliser applicator - Jingang Han; Guobin Wang; Xinyu Xue; Cancan Song; Yubin Lan (Biosystems Engineering, 2026)

Floatable Janus nanofiber membrane driven by photothermal bubbles: A novel platform for efficient photocatalytic water purification - Kelin Wang; Guobin Li; Xiaolong Bie; Jiaqi Yu; Xing Guo; Hanxue Jia; Pengxin Liu; Weimin Kang; Zhenbang Han; Yong Liu (Journal of Cleaner Production, 2025)

Effects of infiltrated rain during the construction stage on the deformation law of a sulphated gravel embankment in regions with seasonally frozen soil - Jinbao Han; Guobin Jing; Shasha Zhang; Qian Yu; Miaoxian Yao; Jingyuan Kou (Soil and Tillage Research, 2025)

Promoted adsorption-photocatalysis synergistic removal of contaminants via surface regulation by a tree-like nanofiber membrane substrate - Minghui Zhang; Zhenbang Han; Guobin Li; Xiaolong Bie; Xingyang Gao; Jin Zhao; Xiaoming Zhao (Journal of Environmental Chemical Engineering, 2024)

MazF-rolling circle amplification combined MALDI-TOF MS for site-specific detection of N6-methyladenosine RNA - Guobin Han; Qiuyuan Lin; Jia Yi; Qian Lyu; Qingwei Ma; Liang Qiao (Analytica Chimica Acta, 2024)

Promoting photo-Fenton reactions by anchoring Fe doped g-C3N4 onto an amidoxime-functionalized fibrous support for organic contaminants removal - Guobin Li; Zhenbang Han; Tao Wang; Minghui Zhang; Qiaoqiao Liu; Tong Zhang; Xiaoming Zhao (Journal of Water Process Engineering, 2023)

Mapping the landscape of ship berthing research: A bibliometric analysis and literature review over two decades - Diao Han; Houzhong Chen; Guobin Song; Tsz Leung Yip; Bing Wu (Ocean & Coastal Management, 2023)

Greenhouse gas emissions from semi-aerobic bioreactor landfills with different vent-pipe diameters - Guobin Jiang; Dan Liu; Weiming Chen; Zhiyong Han; Qibin Li (Environmental Science and Pollution Research, 2021)

Bubble Sweep-Down of Research Vessels Based on the Coupled Eulerian-Lagrangian Method - Wei Wang; Guobin Cai; Yongjie Pang; Chunyu Guo; Yang Han; Guangli Zhou (Journal of Marine Science and Engineering, 2020)
To explore the reason for the bubble sweep-down phenomenon of research vessels and its effect on the position of the stern sonar of a research vessel, the use of a fairing was investigated as a defoaming appendage. The separation vortex turbulence model was selected for simulation, and the coupled Eulerian-Lagrangian method was adopted to study the characteristics of the bubble sweep-down motion, captured using a discrete element model. The interaction between the bubbles, water, air, and hull was defined via a multiphase interaction method. The bubble point position and bubble layer were calculated separately. The spatial movement characteristics of the bubbles were extracted from bubble trajectories. It was demonstrated that the bubble sweep-down phenomenon is closely related to the distribution of the bow pressure field and that the bubble motion characteristics is related to the speed and initial bubble position. When the initial bubble position is between the water surface and the ship bottom, the impact on the middle of the ship bottom is greater and increases further with increasing speed. A deflector forces the bubbles to both sides through physical shielding, strengthening the local vortex structure and keeping bubbles away from the middle of the ship bottom.

Generalized total Kalman filter algorithm of nonlinear dynamic errors-in-variables model with application on indoor mobile robot positioning - Hang Yu; Jian Wang; Bin Wang; Houzeng Han; Guobin Chang (Acta Geodaetica et Geophysica, 2018)